Recent Advancements of Magnetic Nanomaterials in Cancer Therapy - Sudip Mukherjee; Lily Liang; Omid Veiseh (MDPI AG, 2020)
Magnetic nanomaterials belong to a class of highly-functionalizable tools for cancer therapy owing to their intrinsic magnetic properties and multifunctional design that provides a multimodal theranostics platform for cancer diagnosis, monitoring, and therapy. In this review article, we have provided an overview of the various applications of magnetic nanomaterials and recent advances in the development of these nanomaterials as cancer therapeutics. Moreover, the cancer targeting, potential toxicity, and degradability of these nanomaterials has been briefly addressed. Finally, the challenges for clinical translation and the future scope of magnetic nanoparticles in cancer therapy are discussed.